Analysis on the factors associated with COVID-19 infection among Chinese residents after the implementation of the 10 new rules to optimize COVID-19 response: a cross-sectional study - Li, Yunshu; Wang, Sunyi; Yang, Nan; Shi, Yuwen; Yang, Yingxiao; Zhu, Zhixin; Li, Xiuyang (Frontiers in Public Health, 2023)
Abstract Introduction: This study aimed to investigate the status of COVID-19 infection and the associated factors among Chinese residents after the implementation of the 10 New Rules to optimize COVID response. Methods: Participants were recruited using convenience sampling. The study used self-filled questionnaires to examine COVID-19 infection and associated factors among Chinese residents, from December 29, 2022, to January 2, 2023. For the statistical analysis, descriptive and quantitative analyses were used. The potential risk factors for COVID-19 infection were identified by multivariable logistic regression analysis. Results: After the adjustments in control strategies against COVID-19, the infection rate of COVID-19 was high among respondents, and 98.4% of individuals who tested positive showed symptoms including cough, fever, fatigue, headache, sore throat, nasal congestion, sputum production, muscle and joint pain, and runny nose. The main problems respondents reported were the shortage of drugs and medical supplies, the increased burden on families, and the unreliable information source of COVID-19 infection. Logistic regression showed that isolating patients with COVID-19 at home was associated with a lower risk of COVID-19 infection (OR=0.58, 95%CI:0.42-0.81). Conclusions: COVID-19 infection among residents is closely related to age, gender, and epidemic prevention measures. The government needs to strengthen education for individuals and centrally manage and properly address difficulties that may arise during COVID-19. Keywords: COVID-19 infection; regular epidemic prevention and control; related factors; logistic regression; policy analysis.